Challenges for parents of color in children's STEM career aspiration. Issue 2 (25th April 2022) - Oh, Seungbin; Shillingford‐Butler, Ann; Plocha, Aleksandra
Abstract: A wide range of resources have been utilized to promote interest and motivation of students of color in Science, Technology, Engineering, and Math (STEM) professions. Parents have a critical role in supporting their children's career interest and development; however, little literature exists on the unique experiences and challenges faced by parents of color who are involved in their children's career exploration in STEM professions. This phenomenological qualitative study examined the experiences of parents of color regarding their (a) knowledge and beliefs about STEM professions, (b) unique challenges in supporting their children's STEM career interest, and (c) experiences with school counselors in promoting their children's STEM career trajectory. Five resulting themes are discussed, and implications are provided for school counselors.